2019
DOI: 10.1371/journal.pbio.3000309
|View full text |Cite
|
Sign up to set email alerts
|

AMPK regulates germline stem cell quiescence and integrity through an endogenous small RNA pathway

Abstract: During suboptimal growth conditions, Caenorhabditis elegans larvae undergo a global developmental arrest called “dauer.” During this stage, the germline stem cells (GSCs) become quiescent in an AMP-activated Protein Kinase (AMPK)-dependent manner, and in the absence of AMPK, the GSCs overproliferate and lose their reproductive capacity, leading to sterility when mutant animals resume normal growth. These defects correlate with the altered abundance and distribution of a number of chromat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(101 citation statements)
references
References 65 publications
4
96
0
Order By: Relevance
“…Other key signal transduction pathways critical for growth and development that are enhanced in the immature flukes include the (a) AMPK signalling pathway that regulates energy homeostasis and metabolism [ 26 , 27 ] and plays a critical role in the regulation of cell growth [ 28 ]. Recently, Kadekar and Roy [ 29 ] have shown that this pathway is also involved in regulating germline stem cells in Caenorhabditis elegans within the energy-stressed dauer stage via the small RNA pathway; (b) Hippo signalling pathway that regulates organ size through regulation of cellular proliferation and expansion of neoblasts/pluripotent cells during stages of development [ 30 33 ]. As the immature parasites migrate through the liver some of the reproductive organs are at an advanced stage of development, notably the testes which show a clear follicular appearance by 21 dpi in mice [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other key signal transduction pathways critical for growth and development that are enhanced in the immature flukes include the (a) AMPK signalling pathway that regulates energy homeostasis and metabolism [ 26 , 27 ] and plays a critical role in the regulation of cell growth [ 28 ]. Recently, Kadekar and Roy [ 29 ] have shown that this pathway is also involved in regulating germline stem cells in Caenorhabditis elegans within the energy-stressed dauer stage via the small RNA pathway; (b) Hippo signalling pathway that regulates organ size through regulation of cellular proliferation and expansion of neoblasts/pluripotent cells during stages of development [ 30 33 ]. As the immature parasites migrate through the liver some of the reproductive organs are at an advanced stage of development, notably the testes which show a clear follicular appearance by 21 dpi in mice [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next we used Oil Red O to examine fat storage and found that unlike other partial dauer mutants (17), the chd-7;daf-2 abnormal dauers did not exhibit fat-storage deficiencies (Supplementary Figure 1). During the dauer stage, the germ cells remains quiescent to protect their reproductive capacity (41). We observed that germ line in chd-7 mutant dauers was substantially larger than in dauers and appeared to arrest with an L3-like germ line morphology (Figure 1F).…”
Section: Chd-7 Functions In Development Of the Dauer Larvamentioning
confidence: 85%
“…Among other effects, AMPK inhibits the energy utilization hub Mechanistic Target of Rapamycin Complex-1 (mTORC1) under starvation conditions [123], placing cells in an energy conserving, nonproliferative state. The enzyme functions during development of the nematode Caenorhabditis elegans, for example, to induce quiescence in germline stem cells [124]. The quiescence-inducing role of AMPK is conserved across the eukaryotes, also appearing in plants and fungi [125,126].…”
Section: Cessation Of Movement and Quiescencementioning
confidence: 99%